Internalizing the Historical Values of Ternate Island through Novels Mata dan Rahasia Pulau Gapi - Yuni Riyanti; Rouli Esther (Jurnal Sastra Indonesia, 2024)
This research aims to show how children's literature, namely the novels Mata dan Rahasia Pulau Gapi, internalizes the historical values of Ternate Island and their impact on children's behavior in loving historical buildings. The method used in this research is a qualitative descriptive method. The data for this research comes from the novel Mata dan Rahasia Pulau Gapi and non-literary texts, which explain historical facts obtained by close reading. Meanwhile, it was researched using the theory of new historicism to find the harmony between the history depicted in the novel and the historical facts. The results of this research show that the internalization of historical values in the novel Mata dan Rahasia Pulau Gapi seeks to highlight the image of Sultan Khairun and Sultan Babullah and the importance of preserving the historical heritage that is connected to these two sultans, namely the Gamlamo fort or Kastela fort. Apart from that, the internalization of the history of the Dutch occupation, the arrival of Alfred R. Wallace, and the Japanese occupation in the novel Mata dan Rahasia Gapi show how the novel tries to instill an attitude of loving nature.